Transformation in Learning: Interactive and Lecture Methods in Buddhist Education and Ethics at Metta Maitreya Junior High School - Sutikno, Yadi; Hosan, Hosan; Jelita, Rida; Irawati, Irawati; Chowmas, Dharmaji (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study aimed to evaluate the effect of varied and interactive learning methods, such as group discussions, role-playing, and multimedia tools, compared to traditional, lecture-based methods on student learning outcomes in Buddhist and Ethics Education for junior high school students. An experimental design was used with two groups: a control group that followed traditional, lecture-based instruction and an experimental group that applied these varied and interactive methods. The study involved 60 students, evenly divided between the two groups. Research instruments included questionnaires to assess student engagement and motivation, interviews to provide qualitative insights into student experiences, and essay tests to evaluate student learning outcomes. The results indicated that the experimental group achieved a higher average score (85.20) compared to the control group (74.50), with a t-test revealing a significant difference (p 0.01) and a large effect size (Cohen's d = 1.95), indicating a substantial impact of the interactive methods. The study concluded that varied and interactive learning methods demonstrate greater effectiveness in improving student learning outcomes compared to traditional, lecture-based methods. These findings support the use of more dynamic teaching strategies in educational settings, though the study's limitations include a small sample size and lack of longitudinal data. Future research should expand the sample and incorporate long-term analysis to better understand the lasting effects of these methods.